Assessing family processes in depressed patients attending psychiatric clinics of Shahid Beheshti university of Medical Sciences - Ranjbar, Farhdokht; Rahbari, Shahrooz; Mohtashami, Jamileh; Nasiri Oskouyee, Navideh (Advances in Nursing & Midwifery, 2012)
Abstract Background and aim: Depression is an affective disorder which is a common reaction to problematic events. Chaos and disturbance in family processes are considered as risk factor of depression. The aim of this study is to assess the family processes in depressed patients attending to psychiatric clinics of Shahid Beheshti university of medical sciences in Tehran, Iran. Methods and materials. A descriptive design was used for the study. A purposive sample of 180 depressed patients were included in the study. Data were collected by a questionnaire which consisted of two sections. The first section included demographic information and the second part consisted of “ Iranian version of family processes scale”. Validity of the instrument was assured by content validity and reliability was assessed by calculating internal consistency. Data were analyzed by statistical software SPSS17. Results : The overall family processes score for 72.3% of respondents was moderate. The scores for most of patients was highest in religion subscale and lowest for decision making in the family. There was a significant association between religious beliefs and gender. A significant association was also found between decision making and family coherence with marital status ,communication skills and number of siblings. Keywords: Depression. Family processes .Psychiatric clinics